Mevsimlik İş Sözleşmesinin Askıda Olduğu Dönemde İşçi Hakkında Alınan Disiplin Kurulu Kararının Uygulanabilirliği - (:unkn) unknown (My University, 2020)
Atipik bir iş sözleşmesi türü olan mevsimlik iş sözleşmeleri, belirli veya belirsiz süreli iş sözleşmeleri şeklinde akdedilebilecekleri gibi tam veya kısmi süreli iş sözleşmeleri şeklinde de yapılabilirler. Belirli süreli mevsimlik iş sözleşmeleri kural olarak mevsim bitiminde sona ererler. Belirsiz süreli mevsimlik iş sözleşmeleri ise mevsim bitiminden yeni mevsim başlangıcına kadar askıya alınırlar. Mevsimlik iş sözleşmesi mevsim sonunda askıya alındığında işçinin iş görme, işverenin de ücret ödeme borçları ertelenecektir. Sözleşmenin askıda olduğu dönemde mevsimlik işçi hakkında toplu iş sözleşmesi hükümleri uygulanabilir. Bu doğrultuda, işverenin fesih hakkının kullanımı bir disiplin kurulu kararına bağlanmış ise kurul kararı üzerine sözleşme feshedilebilir. Dolayısıyla mevsimlik işçi hakkında sözleşme askıda iken dahi disiplin kurulu kararı uygulanabilir.

Seasonal employment contracts, which are an atypical type of employment contract, can be concluded as fixed or indefinite-term employ?ment contracts, or they can be concluded as full or part-time employment contracts. As a rule, fixed-term seasonal employment contracts expire at the end of the season. The indefinite-term seasonal employment contracts are suspended from the end of the season until the beginning of the new season. When the seasonal employ?ment contract is suspended at the end of the season, worker’s obligation to work and employ?er’s obligation to payment will be postponed. The provisions of the collective labour agree?ment can be applied to the seasonal worker dur?ing the period when the contract is suspended. If the employer’s right of termination depends on the disciplinary board decision, the contract can be terminated upon the decision of the board. Therefore, the disciplinary board decision taken about the worker can be applied even if the contract is suspended.
Applicability of The Disciplinary Board Decision Taken About The Worker During The Period When The Seasonal Employment Contract is Suspended